(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2014)
Research into new forms of energy is a current challenge. This paper aims to inquire into the real advantages of bioenergy and its sustainable development within the European legal framework, while also considering the negative aspects of bioenergy use. The European Union, in fact, is an important supporter of bioenergy and shows that, through good legislative policy, the negative aspects of bioenergy use can be surmounted . In conclusion, bioenergy and sustainable development can still be a plausible solution to feed the planet.